2020
DOI: 10.3389/fpsyg.2020.01325
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Theories and Engagement in Math Among Chinese Adolescent Students: A Moderated Mediation Model of Intrinsic Value and Academic Self-Efficacy

Abstract: Recent studies have established associations between students' implicit theories and their academic engagement. However, there is still limited understanding of the potential mechanisms of this relation, and whether it works for students in the context of mathematics as well as in other subjects. The current study aimed to fill this gap by conducting a two-wave survey examining a moderated mediation model concerning the psychological mechanisms that account for the association between students' implicit theori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Intrinsic value is the degree to which an activity is considered to be personally enjoyable (Chiu and Wang, 2008;Jiang et al, 2020). Straume and Vittersø (2012) claimed that the individuals' feelings of joy or pleasure could affect their behavior.…”
Section: Conclusion Theoretical Contributionsmentioning
confidence: 99%
“…Intrinsic value is the degree to which an activity is considered to be personally enjoyable (Chiu and Wang, 2008;Jiang et al, 2020). Straume and Vittersø (2012) claimed that the individuals' feelings of joy or pleasure could affect their behavior.…”
Section: Conclusion Theoretical Contributionsmentioning
confidence: 99%
“…The scale was adopted from Antony et al (1998) , and was found to be reliable among Chinese sample ( Cao et al, 2023 ). To capture the specific context of the pandemic, we modified it by adding “Because of the COVID-19’’ at the beginning of relevant items (see Jiang et al, 2020 for a similar approach). A sample item is, “Because of COVID-19, I find it difficult to relax.” Students rated the items on a 5-point Likert scale ranging from 1 ( not true at all ) to 5 ( very true ).…”
Section: Methodsmentioning
confidence: 99%
“…As such, enhancement of students’ school performance is of paramount importance. In particular, academic values are significant determinants of academic outcomes ( Jiang et al, 2020 ; Li et al, 2021 ). Past studies have shown that examination scores, school belongingness, engagement in learning, satisfaction with subjects and academic performance, academic self-concept, and psychological well-being of students are related to their academic values (e.g., Katrin et al, 2019 ; Jiang et al, 2020 ; Dou and Shek, 2021 ; Li et al, 2021 ; Wang et al, 2021 ; Allen et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, academic values are significant determinants of academic outcomes ( Jiang et al, 2020 ; Li et al, 2021 ). Past studies have shown that examination scores, school belongingness, engagement in learning, satisfaction with subjects and academic performance, academic self-concept, and psychological well-being of students are related to their academic values (e.g., Katrin et al, 2019 ; Jiang et al, 2020 ; Dou and Shek, 2021 ; Li et al, 2021 ; Wang et al, 2021 ; Allen et al, 2023 ). Nevertheless, striving for academic excellence would create much learning stress and academic anxiety to students ( Xu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%